EFEKTIVITAS MODEL COLLABORATIVE TEAMWORK LEARNING BERBASIS PRAKTIKUM PADA SUB MATERI REAKSI PENGENDAPAN TERHADAP SIKAP ILMIAH DAN HASIL BELAJAR SISWA KELAS XI IPA SMA NEGERI 2 SUNGAI RAYA - Rindha Permata Dewi; Tuti Kurniati; Fitriani Fitriani (Universitas Muhammadiyah Pontianak, 2019)
This study aimed at investigating the effectiveness and the difference of student’s scientific attitude and learning achievement in practicum based collaborative team work learning using expository model in Precipitation Reactions class at the ninth grade Natural Sciences Class of SMA Negeri 2 Sungai Raya. Using a quasi-experimental design, two classes of Natural Sciences participated in this study. In this case, the IPA 1 class was treated as the control group, and the IPA 2 class was treated as the experiment group. The data collection tool of the student’s scientific attitude was an observation sheet, and the tool of the student’s achievement was an essay test. The results of the U-Mann Whitney of SPSS 17,0 showed the difference on the student’s scientific attitude in curiosity, respect on data or facts, critical thinking, open-minded and cooperative attitude, perseverance, and sensitivity (P value (0,000) < α (0,05)). The results also indicated the difference on the student’s learning achievement in control group treated by using practicum-based collaborative team work model, and in control group treated by using practicum-based expository model. The effect size measurement revealed 1.08 (scientific attitude) and 0.96 (learning achievement) and were considered high.